PROTEÇÃO ÀS MARCAS NOTORIAMENTE CONHECIDAS E DE ALTO RENOME / WELL-KNOWN MARKS PROTECTION TO HIGH AND KNOWN - Pereira, Daniel Queiroz; Jacob, Paola Domingues (REVISTA QUAESTIO IURIS, 2013)
DOI: http://dx.doi.org/10.12957/rqi.2013.9579 Trabalho recebido e avaliado pelo Conselho executivo da Revista Quaestio Iuris Resumo O presente artigo tem por objetivo analisar o modo como se dá a proteção às marcas notórias e de alto renome no Brasil. O estudo contempla, ainda, os mecanismos de que se valem as sociedades empresárias para salvaguardar marcas célebres do aproveitamento parasitário e da concorrência desleal. Nesse mister, analisa-se também a possibilidade de reconhecimento da condição de alto renome junto ao INPI possibilitada com o advento da Resolução 107/2013. Palavras-chave: Marcas Notórias, Alto renome, INPI, Concorrência desleal. WELL-KNOWN MARKS PROTECTION TO HIGH AND KNOWN Abstract: The article aims to analyze how highly-reputed and notorious trademarks are protected in Brazil. The study includes the arrangements used by business companies to safeguard their famous trend marks against parasitic use and unfair competition. In these terms, the article analyzes the possibility of recognition the highly-reputed condition by the INPI, possible through the 107/2013 statesman made by INPI. Key words: Notorious trademarks, Highly-reputed, INPI, Unfair competition.